HUMANITARIAN REFORM AND CLUSTER APPROACH: NON-MARKET ORIENTED ACTIONS OF RESOURCE ALLOCATION TO MANAGE TIMOR-LESTE’S HUMANITARIAN CRISIS - Souza e Silva, João Antônio; Irigaray, Hélio Arthur (Perspectivas Contemporâneas, 2014)
There are multiple issues which are relevant to both market and non-market means of resource allocation. When it comes to the former, the lack of precision in general market situations as well as the call for precise relationships between the key concepts: public goods, externalities, accountability and exclusion are highlighted. Indeed, the absence of conditions to assure a Pareto efficient competitive equilibrium situation usually results in resorting to non-market channels of resource allocation, such as government expenditures, taxes, and subsidies, in this case, externalities ought to be studied in terms of criteria, specifically, benefit cost and second-best analyses. For instance, previous international responses to humanitarian emergencies suffered from a lack of accountability, predictability and long-standing gaps in service, especially in the camp management and water and sanitation sectors. In this paper we analyze the case study of two UN agencies and how they used the Humanitarian Reform and the Cluster Approach to allocate resources during and in the aftermath of 2006 crisis in Timor Leste. We carried out a two-year long field research, in Dili, reviewing documents, observing and running questionnaires in order to pinpoint the gaps between the theory and the practice of the non-market actions undertaken by the UN agencies.